ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEMISKINAN DI INDONESIA TAHUN 1999 – 2020 - Pramu, Septian; Hutajulu, Dinar Melani (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2023)
Economic development is one of the factors to increase community welfare. Several factors influence growth, including economic growth and poverty. Poverty, in turn, is influenced by several factors such as literacy, inflation, and unemployment. This research aims to examine the factors that influence poverty in Indonesia from 1999-2020. In this study, the data analysis method used is time series data analysis. Time series data analysis refers to a series of values of a variable over a certain period of time. The variables tested in this analysis include regional minimum wage (UMR), economic growth, inflation, as well as the level of unemployment or poverty (number of poor people), as independent variables that influence the analysis results. The study finds that only literacy and inflation rates have a significant effect on poverty in the long and short term, while unemployment does not have an effect on poverty in Indonesia.